Olive Leaves as a Potential Phytotherapy in the Treatment of COVID-19 Disease; A Mini-Review - Abdelgawad, Shimaa M.; Hassab, Mahmoud A. El; Abourehab, Mohammed A. S.; Elkaeed, Eslam B.; Eldehna, Wagdy M. (Frontiers in Pharmacology, 2022)
Graphical Abstract Plant photo: https://holotropicherbs.com/product/olive-leaf-olea-european-50-gr/